DIVERSITY OF MEDICINAL PLANTS IN NATIONAL PARK OF RINJANI MOUNTAIN IN ORDER TO ARRANGE PRACTICAL HANDOUT OF PHANEROGAMAE SYSTEMATICS - Hudniyati Raslina; Iwan Doddy Dharmawibawa; Safnowandi Safnowandi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2016)
ABSTRACT: National Park is an area of natural resource conservation and ecosystem which is utilized for research, science, education, culture, tourism, and recreation. National Park of Mount Rinjani is located on Lombok island that estimated very high flora diversity. Medicinal plants or herbal are a source of bioactive compounds that efficacious cure various diseases. The purposed of this study was to examine and identify the types of medicinal plants that found in Mount Rinjani National Park area for developing practical handout of Phanerogamae Systematic. This research were descriptive exploratory with qualitative and quantitative approach. Data collection techniques consisted of interviews, observation, validation, test readability by the students, and documentation. The data were analyzed descriptively and techniques percentage. The outcome of this research were form of Practical Handout of Phanerogamae Systematic that developed using 4-D model of modified until step 3, validated by two validators of teaching materials and contents. Practical instructions legibility test by 20 students of Biology Education Program Studies in 6th semester of IKIP Mataram, which has been doing practical to determine the feasibility of practical instructions. The results showed that there are diversity of medicinal plants in Mount Rinjani National Park area with discovery of 34 species of medicinal plants used by people to cure disease. Based on the results of validation by expert instructional materials at rate of 71.4% and content on the level of achievement of 86.3% of eligible used without revision. While the test readability by 20 students of Biology Education in 6th semester showed an average score of 6.68% achievement otherwise unreadable.